Induction of Topographical changes in Poly-ε-Caprolactone scaffolds for bone tissue engineering: biocompatibility and cytotoxicity evaluations - Fernandez, Juan Manuel (2015)
Bone tissue engineering (BTE) uses principles from different fields, such as medicine, biochemistry and engineering, in order to restore or improve damaged tissue. Topographic changes of Poly-ε-caprolactone scaffolds (PCL) have been previously induced by exposure of the polymer to various concentrations of NaOH for different periods of time. However, lack of consistency between the treatment conditions used by different research groups has led to inconsistent results, with no clear conclusion arising regarding the benefits of these treatments. The aim of this study was to evaluate how different treatments (time-concentration) with NaOH could affect its biocompatibility for bone marrow stromal cells (BMSC) and its cytotoxicity towards RAW 264.7 macrophages of a PCL scaffold. We also analyzed the physicochemical and mechanical properties of the PCL films after different treatment. We have shown that treatment with for 2 hours with NaOH produced changes that affected the hydrophobicity and biocompatibility of the scaffold by increasing the proliferation and ALP activity in cells grown on them. Beside, 24 hours of treatment with NaOH produced significant decreased in mechanical properties resulting in a scaffold highly fragile and low biocompatibility compared to PCL. Therefore, treatment for 2 hours with NaOH can be used to increase the biocompatibility of PCL scaffolds.